Dereplication of plant phenolics using a mass‐spectrometry database independent method. Issue 6 (29th May 2018) - Borges, Ricardo M.; Taujale, Rahil; de Souza, Juliana Santana; de Andrade Bezerra, Thaís; Silva, Eder Lana e; Herzog, Ronny; Ponce, Francesca V.; Wolfender, Jean‐Luc; Edison, Arthur S.
Abstract: Introduction: Dereplication, an approach to sidestep the efforts involved in the isolation of known compounds, is generally accepted as being the first stage of novel discoveries in natural product research. It is based on metabolite profiling analysis of complex natural extracts. Objective: To present the application of LipidXplorer for automatic targeted dereplication of phenolics in plant crude extracts based on direct infusion high‐resolution tandem mass spectrometry data. Material and Methods: LipidXplorer uses a user‐defined molecular fragmentation query language (MFQL) to search for specific characteristic fragmentation patterns in large data sets and highlight the corresponding metabolites. To this end, MFQL files were written to dereplicate common phenolics occurring in plant extracts. Complementary MFQL files were used for validation purposes. Results: New MFQL files with molecular formula restrictions for common classes of phenolic natural products were generated for the metabolite profiling of different representative crude plant extracts. This method was evaluated against an open‐source software for mass‐spectrometry data processing (MZMine®) and against manual annotation based on published data. Conclusion: The targeted LipidXplorer method implemented using common phenolic fragmentation patterns, was found to be able to annotate more phenolics than MZMine® that is based on automated queries on the available databases. Additionally, screening for ascarosides, natural products with unrelated structures to plant phenolics collected from the nematode Caenorhabditis elegans, demonstrated the specificity of this method by cross‐testing both groups of chemicals in both plants and nematodes. Abstract : A database independent method for dereplication of phenolics in plant crude extracts based on direct infusion electrospray ionisation mass spectrometry (DI‐ESI‐MS) was achieved using LipidXplorer. Molecular formula restrictions translated into molecular fragmentation query language (MFQL) files for common classes of phenolic natural products were generated for the metabolite profiling of different representative crude plant extracts. The targeted LipidXplorer method implemented using common phenolic fragmentation patterns, was found to be able to annotate more phenolics than MZMine® (open source software) that is based on automated queries on the available databases.